The Derivational Paradigm of the Verb (on the Material of E. Hutsalo Fiction Prose) - Заєць, Валентина Григорівна (Київський національний університет імені Тараса Шевченка, 2018)
The productivity of word-formation types of the verbs has been examined. The analysis of verbal prose formants (usedin Y. Hutsalo’s prose) has been made. The examples confirmed the normative way of verbal wordformation during the period of 80-s years of the previous century. The role and the meaning of formants in verbal models’ formation have been shown. The attention has been focused on the verbal affixes in fiction. The role of word-formation formants for conveying the productivity of action, process, and state has been revealed. The connotative meanings of word-formation means in the text of art prose has been clarified. The role of formant for designation of the beginning of action, dynamism of action, completeness of action has been defined. The role of affixes for designation of non-repeating immediate action, qualitative characteristic of onetime action, procedurality of action has been proven. The formants used for transferring of the qualitative nomination of one-time complete action have been specified. The seldom used by the author affixes, which were used for the explication of a negative evaluation of action reaction effect have been looked upon. Often used formants for producing the word-formation types of verbs in the fiction text have been designated. The possibility of a verb to transfer the dynamics of action has been proved with the examples.

Розглянуто продуктивність словотвірних типів дієслів. Здійснено аналіз дієслівних формантів художньої прози Є. Гуцала. Підтверджено прикладами унормованість дієслівного словотворення в період 80-х років минулого століття. Показано роль і значення формантів у творенні моделей дієслів. Увагу зосереджено на продуктивних дієслівних афіксах художньої прози. Зафіксовано роль словотворчих формантів для передачі продуктивності дії, процесу, стану. З’ясовано відтінки значень словотворчих засобів у тексті художньої прози. Визначено роль формантів на позначення початку дії, динамічності дії, завершеності дії. Розкрито роль афіксів на позначення миттєвої неповторюваної дії, якісної характеристики одноразової дії, процесуальності дії. Указано форманти для передавання якісно-оцінної номінації одноразової завершеної дії. Зауважено про рідковживані письменником афікси для експлікації негативної оцінки дії, зворотної дії. Позначено частовживані форманти для продукування словотвірних типів дієслів у художньому тексті. Доведено прикладами властивість дієслова передавати динаміку дії.
Дериваційна парадигма дієслова (на матеріалі художньої прози Є. Гуцала)
Keywords: affix; derivative; derivative potential; verb; dynamics; normativity; completeness of action; Ukrainian linguistic studies; paradigm; procedurality; word-formation means; formant; афікс; девербативи; дериваційний потенціал; дієслово; динаміка; номінативність; завершеність дії; лінгвоукраїністика; парадигма; процесуальність; словотворчий засіб; формант